Effects of oxyethylated glycerol cryoprotectants on phase transitions of DPPC model membranes - Kasian, N.A.; Krasnikova, A.O.; Vashchenko, O.V.; Lisetski, L.N.; Zinchenko, A.V.; Kompaniets, A.M.; Ratushna, M.V. (Вiopolymers and Cell, 2015)
Aim. To determine the effect of the oxyethylated glycerol cryoprotectants (OEGn) with polymerization degrees n = 5, 25, 30 on the phase states and phase transitions of dipalmitoylphosphatidylcholine (DPPC)-based model membranes. Methods. Differential scanning calorimetry. Results. Model lipid membranes on water/OEGn and water/glycerol subphases with varying cryoprotectant concentrations from 0 to ~ 100 % w/w were studied. A significant raise in the pre-transition and main phase transition temperatures with increasing OEGn concentration was noted whereas the membrane melting peak persist to 100 % w/w OEGn. A sharp increase in the melting enthalpy was observed for OEGn = 5. Conclusions. The solvating ability of the subphase in DPPC membranes decreases in the order water > glycerol > OEGn = 5 > OEGn = 25 > OEGn = 30, which correlates with the relative number of groups effectively contributing to the solvation process. Мета. Встановлення впливу кріопротекторів групи оксиетильованих похідних гліцерину (ОЕГn) зі ступенями полімеризації n = 5, 25 и 30 на фазові стани та фазові переходи модельних ліпідних мембран на основі ДПФХ. Методи. Диференціальна скануюча калориметрія. Результати. Досліджено модельні ліпідні мембрани на субфазі вода/ОЕГn та вода/гліцерин із варіюванням концентрації кріопротектору від 0 до ~100 мас. %. Зі збільшенням концентрації ОЕГn суттєво зростають температури передпереходу та плавлення модельної мембрани, при цьому пік плавлення зберігається до 100 мас. % ОЕГn. Для ОЕГn=5 віднайдено значне зростання ентальпії плавлення мембрани. Висновки. Сольватуюча здатність субфази, що оцінена по зниженню температури плавлення сухого ДПФХ, знижується у низці вода > гліцерин > ОЕГn=5 ОЕГn=25 ОЕГn=30, що корелює зі зменшенням питомої кількості груп, що ефективно беруть участь у сольватації. Цель. Установление влияния криопротекторов группы оксиэтилированных производных глицерина (ОЭГn) со степенями полимеризации n = 5, 25 и 30 на фазовые состояния и фазовые переходы модельных липидных мембран на основе ДПФХ. Методы. Дифференциальная сканирующая калориметрия. Результаты. Исследованы модельные липидные мембраны на субфазе вода/ОЭГn и вода/глицерин с варьированием концентрации криопротектора от 0 до ~100 масс. %. С увеличением концетрации ОЭГn существенно возрастают температуры предперехода и плавления модельной мембраны, при этом пик плавления сохраняется вплоть до 100 масс. % ОЭГn. Для ОЭГn=5 обнаружено значительное возрастание энтальпии плавления мембраны. Выводы. Сольватирующая способность субфазы, оцененная по снижению температуры плавления сухого ДПФХ, снижается в ряду вода > глицерин > ОЭГn=5 > ОЭГn=25 > ОЭГn=30, что коррелирует с уменьшением удельного количества эффективно участвующих в сольватации групп.